Influence of pasteurization treatment and storage in the red colour and microbiological stability of pomegranate juice - Vegara S.; Funes S.; Mena P.; Martí N.; Saura D.; Valero M. (II International Symposium on the Pomegranate, 2012)
The combination of time and temperature of pasteurization treatments and storage conditions are critical in the degradation of the organoleptic and microbiological stability of juice. Therefore, the influence of pasteurization (high and low temperature) and storage conditions (refrigerated and room temperature) on the variation of the red color and microbiological stability of processed juice was evaluated. Both pasteurization treatments were effective in reducing microbial load and keeping the juice stable over time. However, storage temperatures had been decisive, because the juices stored at 25°C had lost 70-80% of its original red color.
2. International Symposium on the Pomegranate, 2011/10/19-21, Madrid (Spain)